Red para el deporte paralímpico en Armenia (2021)
The project is developed under the idea of having spaces associated with structuring systems in the city. So it is determined to develop a park since they are spaces that serve as nodes of interaction between the population thanks to these you can protect the fauna and flora of the cities, promote activities of recreation, sport, landscaping and education. They promote the growth of societies and strengthen their ties. From the above, it was determined that the design would focus on the creation of a sports park to help promote Paralympic sport, since these types of sports are often discriminated against in societies. All this having as a problem to solve that developing cities are not being designed to be accessible to disabled populations, where cities do not have suitable spaces for a physically or visually impaired person to move on his or her own.